The Police negligence in crime enforcement efforts: Ethical sanctions or criminal punishment - Anizar Ayu Pratiwi; Fadli Rahman Wahidi (Priviet Social Sciences Journal, 2026)
Polri is an institution that participates in its duties and responsibilities to provide service, care and protection to the community. Police attitudes and ethics are regulated in the Code of Ethics and Guidelines for the Conduct of the Polri to limit and avoid arbitrariness and abuse of power, including police negligence in carrying out their duties and responsibilities. The purpose of this study is to determine the ethical and criminal sanctions for Polri’s member and the limitations of ethical and criminal sanctions for police negligence in carrying out their duties. The research method used in this writing is theoretical research based on primary, secondary, and tertiary data sources. Polri as one of the professions, upholds ethics and behavior in carrying out their duties. Any member of the police who violates ethical and disciplinary provisions may be subject to ethical sanctions in accordance with the applicable code of ethics. Meanwhile, legal violations and criminal acts committed by the police can be subject to criminal penalties just like the general public, and thru the applicable criminal justice process and criminal procedure law. Ethical and disciplinary sanctions do not negate criminal penalties, nor do criminal penalties negate ethical sanctions; these sanctions can be applied concurrently